Impact of the Greek Diaspora on Translations of Modern Greek Literature in Slovakia - Mokošová, Renáta (Sapiens ubique civis, 2023)
This paper presents some of the results of a PhD research concerning translations of Modern Greek literature into Slovak language. It will focus on the comparison of the translation activities in Slovak and Czech Republic. It is a well-known fact that there is an abysmal difference between the Czech and Slovak translation situation for what Modern Greek literature concerns. After the defeat of the communists in Greece in 1949, Czechoslovakia received thousands of Greek citizens who were stationed only in cities of the Czech part of the country. The first lectorate of Modern Greek was established at the Charles University in Prague in order to educate Greek children in their mother tongue. Textbooks and dictionaries in Czech language were published to help Greeks integrate themselves in the new environment. The situation in the Slovak part of Czechoslovakia was diametrically different. The absence of a Greek diaspora had a significant impact on Modern Greek studies and hence the production of translations from Modern Greek literature into Slovak.